Implikasi Hukum Perjanjian Jual Beli Tiket Konser Tidak Resmi Terhadap Konsumen - Almira Fadilla, Rizkia; Fitriyanti, Fadia (Magister Kenotariatan, Universitas Jambi, 2026)
This study discusses the legal implications of unofficial concert ticket sales agreements from a civil law perspective. The practice of selling tickets through unauthorized parties creates legal uncertainty and financial losses for consumers, as tickets purchased may not be recognized by the concert promoter. This research employs a normative juridical method using statutory and case approaches. The results show that such agreements fall under innominaat contracts (unnamed contracts), which may be deemed null and void if they do not fulfill the lawful cause requirement under Article 1320 of the Indonesian Civil Code. Legal protection for consumers is regulated in Law No. 8 of 1999 on Consumer Protection and Law No. 11 of 2008 on Electronic Information and Transactions. Strengthened supervision and synergy among the government, consumer protection institutions, and digital platforms are essential to ensure effective consumer legal protection in digital transactions.